Evaluation of Promising Lines and Biofortified Varieties of Wheat in Tikapur, Kailali, Nepal - Sharma, Raksha; Rajbanshi, Devraj; Bohara, Binod; Magar, Sangita Gaha; Sharma, Ganesh (Agronomy Journal of Nepal, 2024)
Variety is one of the major factors affecting the productivity of wheat in Nepal. To compare the performance of promising lines, zinc fortified wheat and popular varieties of wheat, the field experiment was laid out in randomized complete block design at Agronomy farm of Far Western University, Tikapur, Kailali during November 2022. Observations were made on the growth stages, plant height, yield attributing traits and yields. The results revealed significant variation among the varieties at 5% level of significance. Among the promising lines compared, NL 1451 was significantly superior (p≤0.05) in yielding the number of effective tillers (338), grains per spike (48), grain yield (3.79 t ha-1) and straw yield (7.07 t ha-1) but BL 4951 had significantly smallest plant height and spike length. Similarly, NL 1446 also performed better after NL 1451 yielding more than 3.5 t ha-1. Among the recommended varieties compared, Zinc gahun-2 performed poorly than Zinc gahun-1 in all the parameters except for total tiller count, effective tiller count, grain filling period and peduncle length. BL 4951 outperformed all the Nepal lines and varieties in plant height and spike length but could not perform better in other parameters.